Aborto retenido con degeneración vesicular - Remy Paredes, Nicola (2021)
36-year-old female patient with amenorrhea for 6 weeks, enters the emergency service of gynecology and obstetrics for pelvic pain associated with scarce vaginal bleeding and increased uterus size for the gestational age, elevated b-hcg levels and a suspected molar pregnancy. An mva is performed evidencing ovular remains and pearl vesicules characteristics of the pathology in mention, however, the results of pathological anatomy report fetal death to decart bad fetal maternal perfusion. From this case, the different forms of presentation that a retained abortion may present are rescued.